(3af GdJQLeI GdEYdGejI aj hSGFd GdGJUGd GdLeGgjQj (B:s (3TQM cGed dCUhd h bhGYO GdJQLeI GdEYdGejI(B- (3TQM cGed dbhGYO GddZI GdGfLdjRjh GdhXjajI(B- (3JOQjHGJ h JWHjbGJ TGedI Ydi GdJQLeI GdEYdGejI(B- (3JYHjQGJ h eUWdMGJ EYdGejI (B/s - (3TcQj, YHO GdeLjOs ((3GdbGgQI (B:s (3OGQ GdacQ GdYQHj ,s, 2004)
(3gcPG LGA gPG GdcJGH GdLOjO JOQjLjG deLehY GfJGLg GdYdej GdeJejR h djSO aQGZG cHjQG aj eLGd GdOQGSGJ GdEYdGejI Hd dYdg GdcJGH GdhMjO aj gPG GdJNUU GdfGOQ h gh GdJQLeI GdGYdGejI GdJj GUHMJ VQhQI dG Zfi YfgG ddeTJZdjf HGdYed GdGYdGej aj GdUMGaI h GdQGOjh h GdJdjaRjhf hhcGdGJ GdGfHGA h dLejY WdGH cdjGJ h GbSGe GdGYdGh GdGYdGe GdJQHhj aj GdLGeYGJ GdeUQjI h GdYQHjI h WdGH s
Keywords: (3GdGJUGd GdLeGgjQjs; (3GdJQLeI s; (3hSGFd GdEYdGe s